Herpes zoster duplex bilateralis symmetricus in an immunocompromised patient with recent varicella infection - Nuntouchaporn Amonchaisakda (2022)
A single varicella infection usually causes lifelong immunity, so recurrent varicella infection is considered rare. Reactivation of the virus as herpes zoster usually develops after a latent period. Here, we report a case of a 48-year-old immunosuppressed patient who presented with rapid-onset symmetrical bilateral papulovesicular eruptions on both legs 3 weeks after having recurrent varicella infection that had been treated with intravenous acyclovir. Varicella zoster virus (VZV) Ag testing was performed on vesicular lesions. The positive result confirmed that VZV had reactivated. It presented in the form of herpes zoster duplex bilateralis symmetricus. This condition is rare and occurs primarily in immunocompromised female hosts.